The Influence of Career Patterns on Work Motivation of Air Traffic Controllers at Jakarta Air Traffic Service Center (JATSC) - Waskhito Tri Hutomo; Elfi Amir; Dwi Lestary (CV. AFDIFAL MAJU BERKAH, 2026)
The profession of Air Traffic Controller (ATC) at the Jakarta Air Traffic Service Center (JATSC) carries a critical responsibility for maintaining aviation safety in one of Southeast Asia’s busiest airspaces. Given the high-pressure environment in which ATCs operate, work motivation plays a vital role in sustaining performance and minimizing human error. This study aims to analyze the influence of career patterns on ATC work motivation at JATSC. Using a quantitative descriptive-correlational method, data were collected from 89 ATC personnel selected through purposive sampling. Primary data were obtained using a Likert-scale questionnaire supported by observation and documentation. Data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression to test the hypothesis. The results revealed a significant positive relationship between career patterns and work motivation, indicating that clearer and more transparent career structures enhance motivation and performance. Moreover, respondents perceived that limited promotion opportunities and unclear advancement pathways could potentially decrease long-term motivation. The findings underscore the importance of implementing a structured and competency-based career management system to sustain ATC motivation and operational safety. These results provide empirical evidence and managerial implications for AirNav Indonesia to improve career development policies that promote fairness, transparency, and professional growth